Authenticity study of Phyllanthus species by NMR and FT-IR Techniques coupled with chemometric methods - Maiara S. Santos; Edenir R. Pereira-Filho; Antonio G. Ferreira; Elisangela F. Boffo; Glyn M. Figueira (Química Nova, 2012)
The importance of medicinal plants and their use in industrial applications is increasing worldwide, especially in Brazil. Phyllanthus species, popularly known as "quebra-pedras" in Brazil, are used in folk medicine for treating urinary infections and renal calculus. This paper reports an authenticity study, based on herbal drugs from Phyllanthus species, involving commercial and authentic samples using spectroscopic techniques: FT-IR, ¹H HR-MAS NMR and ¹H NMR in solution, combined with chemometric analysis. The spectroscopic techniques evaluated, coupled with chemometric methods, have great potential in the investigation of complex matrices. Furthermore, several metabolites were identified by the NMR techniques.